Correlation of rheological parameters in maternal and fetal blood at term. (May 2015) - Csorba, Roland; Soliman, Amr A.; Wieg, Christian; Tsikouras, Panagiotis; Rath, Werner; von Tempelhoff, Georg-Friedrich
Abstract Objective: An association between maternal and fetal blood rheology has not yet been investigated nor is it known whether and to what extent fetal blood rheology may be affected by maternal conditions. Methods: At delivery, blood was drawn from the cubital vein of 4985 consecutive mothers and from the umbilical cord during birth for determination of blood rheological parameters (erythrocyte aggregation stasis [E0], low shear [E1], plasma viscosity [Pv]) in addition to hemoglobin (Hb) values and hematocrit (Hct). Results: Maternal and newborn Pv (r = 0.2; p < 0.0001) correlated statistically significant. There was a remarkable correlation between fetal Pv and gestational age (r = 0.197; p < 0.001). Iron supplementation during pregnancy led to increased fetal Hb, Hct as well as E0 and E1 (p < 0.0001), did not have a significant impact on neonatal Pv (p = 0.068). Smoking mothers gave birth to neonates with significantly higher Pv (p = 0.049), E0 (p = 0.016) and E1 (p = 0.013). Conclusions: The increase of fetal plasma viscosity at advanced delivery time-points refers to a more gaining protein synthesis by the fetal liver and thus maturity of the fetus. Iron supplementation as well as smoking during pregnancy is associated with a relative hyper-viscosity in the fetus at delivery.